An open‐label study to estimate the effect of steady‐state erythromycin on the pharmacokinetics, pharmacodynamics, and safety of a single dose of rivaroxaban in subjects with renal impairment and normal renal function. (3rd July 2014) - Moore, Kenneth T.; Vaidyanathan, Seema; Natarajan, Jaya; Ariyawansa, Jay; Haskell, Lloyd; Turner, Kenneth C.
Abstract Two previously conducted rivaroxaban studies showed that, separately, renal impairment (RI) and concomitant administration of erythromycin (P‐glycoprotein and moderate cytochrome P450 3A4 [CYP3A4] inhibitor) can result in increases in rivaroxaban exposure. However, these studies did not assess the potential for combined drug–drug–disease interactions, which—in theory—could lead to additive or synergistic increases in exposure. This study investigated rivaroxaban pharmacokinetics and pharmacodynamics when co‐administered with steady‐state (SS) erythromycin in subjects with either mild or moderate RI. Similar to previous studies, rivaroxaban administered alone in RI subjects, or when co‐administered with SS erythromycin in normal renal function (NRF) subjects, increased rivaroxaban exposure. When combined, the co‐administration of rivaroxaban 10 mg with SS erythromycin in subjects with mild or moderate RI produced mean increases in rivaroxaban AUC∞ and Cmax of approximately 76% and 56%, and 99% and 64%, respectively, relative to NRF subjects, with PD changes displaying a similar trend. No serious adverse events occurred and no persistent adverse events were reported at the end of study. Although these increases were slightly more than additive, rivaroxaban should not be used in patients with RI receiving concomitant combined P‐glycoprotein and moderate CYP3A4 inhibitors, unless the potential benefit justifies the potential risk.